g.640T>C Polymorphism of the TGF-Î²2 Gene is Associated with Salmonella pullorum Resistance in Indonesian Chickens - Muhsinin, Muhammad; Ulupi, Niken; Gunawan, Asep; Wibawan, I Wayan Teguh; Sumantri, Cece (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2017)
The objectives of this study were to identify polymorphism of transforming growth factor Î²2 (TGF-Î²2) gene associated with Salmonella pullorum resistance in Indonesian chickens. Polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) assays were used to genotype Indonesian chickens. Analysis of polymorphism was conducted by using PopGen 3.2 software. The effect of genotype on S. pullorum resistance was analyzed using the SAS General Linear Model (GLM) procedure. Genotyping was performed on 278 chickens from 7 Indonesian chicken populations (Sentul, Merawang, Pelung, Kampung, Parent Cobb broiler, The F1 crossbreed of Kampung x Parent Cobb broiler (KB) and F2 KB x KB. The product of amplification was 284 bp. The TGF-Î²2| RsaI locus was polymorphic in all populations, producing two alleles (T and C) and three genotypes (TT, CT, and CC). The result from the analysis of the allele and genotype frequency showed that the T allele had a higher frequency than the C allele in all populations. The Ï‡2 analysis showed that the 6 chicken populations were deviated from Hardy-Weinberg equilibrium, with the exception of the Parent Cobb broiler chicken. The association result showed that TT genotype was significantly associated with S. pullorum resistance in Sentul chicken. Although the leukocyte concentration, leukocyte differentiation and H/L ratio in Sentul chicken with three of TGF-Î²2 genotypes (TT, TC, and CC) were not statistically different. In conclusion, polymorphism in the TGF-Î²2 chicken gene can be used as a candidate marker to increase S. pullorum immune response.